Comparison of Alexithymia and conscious emotion (shame and guilt) in women with major depressive disorder and normal women - Vaezfar, Saeedeh; Rezaei, Azarmidokht (Psychology of Woman Journal, 2020)
The present study aimed to compare Alexithymia and unconscious emotions in women with major depressive disorder and normal women. The design of the current research was a causal-comparative description. The current study’s statistical population was comprised of all women with major depressive disorder and normal women in Shiraz city in 2017. From the statistical population, 70 women with major depressive disorder and 70 normal women were selected by the method available were selected and studied. Tangney’s (1992) and Toronto’s Alexithymia (1986) questionnaires were administered to each subject. After collecting and extracting the data, the participants’ scores were analyzed using multivariate analysis of variance. The results of multivariate variance analysis showed a significant difference between conscious emotion and Alexithymia in women with major depressive disorder and normal women.